Achieving conservation: new cognitive based zoo design guidelines - Ploutz, Russell (Kansas State University, 2014)
Typical aspects of a zoo’s mission are conservation of wildlife and habitats. As part of conservation efforts zoos provide opportunities for visitors to learn about animals and their environments. Ultimately their goal is visitor understanding leading to conservation behavior. While documented zoo design methods such as landscape immersion, cultural resonance and interpretation elements provide opportunities to learn, current literature stops short of explaining how visitors learn. This research intends to bridge this gap through an innovative mixed methods approach under the hypothesis: if designers understand how visitors learn, their design approach will change to integrate learning and cognitive process theories, resulting in exhibit designs which engage visitor’s cognitive processes increasing learning, thereby increasing the potential for conservation behavior. A thorough literature review revealed cognitive psychology and learning theories vital to exhibit design. Cognitive processes are the mental processes visitors use to learn, think and act (Leonard, 2002). To design for visitor’s cognitive processes designers need to be concerned with visitor’s attention, perception, recall, understanding and memory (Koran, 1983). A personal design exercise testing novel approaches for incorporating cognitive processes into theoretical exhibits yielded potential new guidelines and typologies for exhibit design. To test these personal insights, integrated survey and participatory methods were envisioned to engage zoo design professionals. Professional zoo exhibit designers attended two workshops where they learned about cognitive processes and learning theories, discussed and sketched ideas for learning in zoos, and focused on how to integrate theories in design. The interactive charrette engaged zoo design professional’s cognitive processes to uncover new approaches and typologies for zoo exhibit design. Participants completed pre and post-surveys to measure design approach changes. Chan’s (Chan, 2001) five components of an individual’s design style are used as a framework for the survey questions. Results from the workshop suggest participants augmented their design approach by increasing the influence of cognitive processes in their design approach and concepts. Participants also showed an increased ability to create goals for learning and an increased ability to form constraints along with improvements in existing mental imagery. Additionally, participants demonstrated increases in their search pattern and order in typical design stages of research, site analysis and design development. From the workshop analysis of the surveys, discussions, and sketches, new design strategies emerged to guide the design of exhibits in engaging and facilitating visitor’s cognitive processes. A triangulation analysis methodology validated the design strategies creating 53 design guidelines for learning by comparing design strategies in the workshop, personal charrette and literature. The design guidelines are compiled into an interactive PDF for other zoo designers and professionals use. To assist the reader in employing the design guidelines most effectively learning principles explain the fundamental learning concepts grounding the guideline. Also, seven example projects illustrate the use of the guidelines. The guidelines, learning principles and example projects are hyperlinked to facilitate learning and application.
Keywords: Zoo design; Landscape architecture; Learning theory; Cognitive psychology; Design guidelines; Cognitive Psychology (0633); Landscape Architecture (0390); Museum Studies (0730)